Work-family conflict among female nurses in the healthcare sector - Kengatharan, N.; Kunatilakam, S. (My University, 2020)
The research drew on gender role ideology, conservation of resources and social identity theory to explore the relationships between work–family conflict, emotional intelligence, leadermember exchange, employee engagement and job performance. Data were collected using selfreport questionnaires from 169 female nurses working in three major hospitals in Sri Lanka. The study found that work–family conflict was negatively related to employee engagement and job performance. However, the negative relationship between work–family conflict and job performance turned out to be positive at a higher level of emotional intelligence. The study further found that the negative relationship between work–family conflict and employee engagement was weaker for those reporting a higher level of leader–member exchange. The study contributes to the extant literature by unearthing theoretical relationships in the healthcare sector. The implications of the study, limitations and directions for future research are also discussed.
Keywords: Emotional intelligence; Employee engagement; Job performance; Leader-member exchange; Work-family conflict